ECONOMIC DEVELOPMENT PLANNING MODELS: A THEORETICAL AND ANALYTICAL EXPOSITION - Kolawole, Bashir Olayinka (European Scientific Journal, ESJ, 2013)
This paper explores some planning models that have, in one period or the other, been employed by both developed and less developed countries to forge development of their respective economies. Using theoretical basis of analysis, the paper shows that while some models are weak in their applicability, certain models like the Leontief Input-Output model and the Linear programming model, however, are relevant in efficacy to the development of economies via sectoral and inter-industry interdependence, aggregate demand, and growth in output.